Visual outcome and rotational stability of open loop toric intraocular lens implantation in Indian eyes - Arvind Venkataraman (Indian Journal of Ophthalmology, 2013)
Purpose: To assess the visual outcome and rotational stability of single-piece open loop toric Intra Ocular Lens (IOL) in a clinical setting. Materials and Methods: In a prospective study, 122 eyes of 77 patients were followed up for a period of 12 months after cataract surgery with toric open loop IOL implantation. The pre-operative markings for the position of incision and IOL placement were done under slit lamp by anterior stromal puncture. The visual acuity, refraction, and IOL position were assessed at day 1, 1 week, 1 month, 3 months, 6 months, and 12 months after surgery. Results: The mean age of the cohort was 56 yrs (S.D. 13.88; range 16 to 87 years). The mean pre-operative cylinder of corneal astigmatism was 1.37 D. (SD 0.79, range 1.0 to 5.87 D). Mean post-operative refractive cylinder was 0.36 D (SD 0.57, range 0 to 1.50 D) at 12 months. Ninety-seven percent of the eyes were within 1 D of residual astigmatism. Ninety-four percent of patients had uncorrected visual acuity of 20/30 or better. Four eyes required IOL repositioning due to rotation. At 12 months, 96.7% of the IOLs were within 10 degrees of the target axis. There was no rotation seen after 6 months. Conclusion: Toric IOLs are very effective and consistent in correcting astigmatism during the cataract surgery. IOL rotation happens mostly within a month of surgery, and if significant, requires early repositioning.